HEALTH WORKER STRATEGY TO INCREASE MATERNAL PARTICIPATION IN INFANT IMMUNIZATION IN MEKAR BARU BATUBARA REGENCY - Fadillah, Amalia Rahma; Yunus, Saifuddin; Rizki, Dini (FISIP Universitas Malikussaleh, 2025)
This study examines health workers' strategies to increase mothers' participation in immunization (case study of Mekar Baru Village, Datuk Tanah Datar Sub-district, Batubara District). The main focus in this study is the cause of mothers refusing to immunize their children and how the health worker's strategy in increasing maternal participation in immunization implementation. This study uses Max Weber's social action theory. The research method used in this research is a qualitative method with a descriptive approach. The data in this study comes from primary data, namely observation and interviews, while the secondary data in this study is documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the causes of mothers refusing to immunize were a) the mother's experience of immunization side effects, b) the mother's perception of immunization. In optimizing and increasing participation, a strategy is needed, as for the strategies carried out by Petatal health center health workers in increasing and optimizing immunization participation in Mekar Baru Village are a) Conducting immunization socialization to parents, especially mothers and b) direct visits to the homes of mothers whose children have not received complete immunization.